2022
DOI: 10.1002/gps.5776
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between handgrip strength, depression and cognitive functioning among older adults: Evidence from longitudinal ageing study in India

Abstract: Background Handgrip strength (HGS) is a frequent and general indicator of muscle strength and it may affect several aspects of mental health among older people. This study explored the association of HGS with depression and cognitive impairment among community‐dwelling older adults in resource‐constrained setting of India. Method Data were drawn from the Longitudinal Ageing Study in India (LASI), and the analysis was conducted on 27,707 older adults aged 60 years and above. Outcome measures included depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Its simplicity, portability, and low cost make it an attractive tool for assessing individual health risks ([38]). Previous research into grip strength and depression has indicated that weak grip strength might be a risk factor for depression in middle-aged and elderly individuals [39][40]. These studies have suggested a doseresponse relationship between grip strength and depression risk, highlighting a negative correlation between grip strength and the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Its simplicity, portability, and low cost make it an attractive tool for assessing individual health risks ([38]). Previous research into grip strength and depression has indicated that weak grip strength might be a risk factor for depression in middle-aged and elderly individuals [39][40]. These studies have suggested a doseresponse relationship between grip strength and depression risk, highlighting a negative correlation between grip strength and the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Since standards based on high-income countries pose a considerable problem in properly assessing grip strength, the reference standards for phenotypically different Indian populations were used in the current study. Thus, the cut-off for weak HGS for males was 19.5 kg; for females, it was 12.5 kg, taken as the lowest 25th percentile or lowest quartile, validated in the Indian context 39 41 . Sensitivity analysis was conducted using a cut-off suggested by the Asian Working Group on Sarcopenia, with less than 28 kg for males and less than 18 kg for females 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Sức mạnh cơ chi trên trung bình của nhóm người bệnh có suy giảm nhận thức thấp hơn có ý nghĩa thống kê so với nhóm người bệnh không bị suy giảm nhận thức (14,8 kg so với 21,7 kg). Có điểm tương đồng trong một nghiên cứu theo chiều dọc ở Ấn Độ, cũng thấy mối liên quan giữa suy giảm nhận thức với cơ lực tay, những người cao tuổi tham gia nghiên cứu có cơ lực tay yếu có khả năng bị suy giảm nhận thức cao hơn (B: 0,92, CI: 0,76-1,07) so với những người có cơ lực tay mạnh [10].…”
Section: Bàn Luậnunclassified